EDUKASI LITERASI HALAL PADA WIRAUSAHA GEN Z - Haryanti, Peni; Sopingi, Imam; Hidayati, Athi'; Yuni K, Kusnul Cipta Nila; Musfiroh, Anita; Santoso, Rohmad Prio; Ali, Muhammad Haidar (ABIDUMASY, 2024)
The number of Gen Z entrepreneurs in the 2024 KDLK Entrepreneurship Program at Unhasy who hold halal certification is less than half of the total participants. Additionally, their knowledge and understanding of halal assurance are limited. To address this issue, the Community Service Team from the Islamic Economics Study Program, Faculty of Economics at Unhasy, conducted a halal literacy education program for Gen Z entrepreneurs participating in the KDLK Entrepreneurship Program. Prior to this, the participants had never received similar halal literacy training. The program aims to enhance the quality of Gen Z entrepreneurs' products in the future through halal certification, enabling them to sustain and compete in the modern world. The activity also supports students without halal certification to independently register their businesses using the self-declare halal certification mechanism, facilitated by the community service team. The results show that all students in the KDLK Entrepreneurship Program successfully registered halal certification for their businesses.